2005
DOI: 10.1158/0008-5472.can-04-3263
|View full text |Cite
|
Sign up to set email alerts
|

Development of Skin Tumors in Mice Transgenic for Early Genes of Human Papillomavirus Type 8

Abstract: The cutaneous human papillomavirus (HPV) 8 is clearly involved in skin cancer development in epidermodysplasia verruciformis patients and its early genes E2, E6, and E7 have been implicated in cell transformation in vitro. To examine the functions of these genes in vivo we integrated the complete early region of HPV8 into the genome of DBA/Bl6 mice. To target their expression to the basal layer of the squamous epithelia the transgenes were put under the control of the keratin-14 promoter. Transgenic mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
178
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(194 citation statements)
references
References 35 publications
11
178
1
2
Order By: Relevance
“…34 Overall, our results indicated that E4 staining could be exploited as a marker of viral expression during b-HPVassociated skin cancer progression as reported in the HPV8 transgenic mouse model and in cervical disease for the a-genotypes. 33,[45][46][47] To extend the data obtained so far in epidermodysplasia verruciformis patients to other groups of patients at high risk of developing skin cancer, here we studied a series of skin lesions from kidney transplant recipients attending our University Hospital by systematically analyzing for the presence of b-HPV infection both at the DNA (PCR) and protein level. Using a combination of antibodies raised against the E4 and L1 proteins of the b-genotypes, we were able to visualize the completion of viral life cycle in some precancerous lesions such as actinic keratosis or at the periphery of more advanced disease.…”
mentioning
confidence: 99%
“…34 Overall, our results indicated that E4 staining could be exploited as a marker of viral expression during b-HPVassociated skin cancer progression as reported in the HPV8 transgenic mouse model and in cervical disease for the a-genotypes. 33,[45][46][47] To extend the data obtained so far in epidermodysplasia verruciformis patients to other groups of patients at high risk of developing skin cancer, here we studied a series of skin lesions from kidney transplant recipients attending our University Hospital by systematically analyzing for the presence of b-HPV infection both at the DNA (PCR) and protein level. Using a combination of antibodies raised against the E4 and L1 proteins of the b-genotypes, we were able to visualize the completion of viral life cycle in some precancerous lesions such as actinic keratosis or at the periphery of more advanced disease.…”
mentioning
confidence: 99%
“…A similar classification would greatly help elucidate the role of cutaneous HPV types in SCCC and skin carcinoma. The early genes of HPV8 have been shown to be expressed in the epidermis and to induce spontaneous benign and malignant skin lesions in transgenic mouse models (Schaper et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The beta HPV types were first isolated in skin cancer-prone patients suffering from a rare autosomal recessive genetic disorder called epidermodysplasia verruciformis, but it is now clear that they are commonly found in the skin of healthy individuals (Pfister, 2003). Characterization of the biological properties of the products of the early genes E6 and E7 from different beta HPV types in in vitro and in vivo model has highlighted the potential carcinogenicity of these viruses (Jackson et al, 2000;Caldeira et al, 2003;Akgul et al, 2005;Dong et al, 2005;Schaper et al, 2005;Accardi et al, 2006;Michel et al, 2006). We showed that expression of E6 and E7 from the beta HPV38 in primary human keratinocytes results in inactivation of the tumour suppressor p53 and pRb and immortalization (Caldeira et al, 2003;Accardi et al, 2006).…”
mentioning
confidence: 99%